SUSTAINABILITY IN TEXTILES: A CRITICAL REVIEW OF ECO – FRIENDLY PRACTICES AND MATERIALS - Sawant, Jyoti; Guru, Ramratan; Grewal, Deepika; Talekar, Sunil Changdev; Kulkarni, Swapanali Parveen (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sustainability in textiles, focusing on eco-friendly practices and materials. The paper examines the multifaceted approaches adopted by the fashion industry to mitigate environmental impact and promote ethical production. It scrutinizes the adoption of eco-conscious practices, such as utilizing organic fibers, recycled materials, and innovative biodegradable textiles. Through an analytical lens, the review evaluates the efficacy of these eco-friendly measures in reducing the industry’s carbon footprint, minimizing waste, and conserving natural resources. It delves into the challenges faced in the widespread adoption of sustainable practices, considering issues related to scalability, cost-effectiveness, and consumer adoption. Further more, the review assesses the social and ethical dimensions of sustainable fashion, emphasizing fair labor practices, supply chain transparency, and the empowerment of communities involved in textile production. Drawing upon a comprehensive analysis of scholarly articles, industry reports, and case studies, this review critically examines the progress, limitations, and future prospects of sustainability in fashion and textiles, providing insights for researchers, practitioners, and policymakers in advancing eco-friendly practices within the industry.